Gambaran Pengetahuan Dan Sikap Petani Tentang Penggunaan Pestisida Pada Kelompok Tani Ranah Bingkuang Di Nagari Lalan Kecamatan Lubuk Tarok Kabupaten Sijunjung - Danhas, Zeswita A.L., Y; Prihartono, A T (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2026)
Farmers in Lubuk Tarok Subdistrict still rely on chemical pesticides to control rice pests (such as planthoppers and stem borers) in order to protect their crops. Most farmers do not understand the negative effects of pesticide use on the body, so none of them use personal protective equipment (PPE) when applying pesticides in their fields. The purpose of this study was to determine the farmers' knowledge and attitudes regarding pesticide use in the Ranah Bingkuang Farmer Group in Lalan Village, Lubuk Tarok District, Sijunjung Regency. This study used a quantitative research design with a descriptive approach. This research was conducted in Lalan Village, Lubuk Tarok District, Sijunjung Regency. The research was conducted in September 2025. The population consisted of 30 people, and all members of the population were used as research samples. Data collection was carried out using questionnaires, and data processing was done using computers, namely editing, coding, entry, cleaning, and analyzed univariately using descriptive statistics in the form of frequency distribution and percentages. The results of this study show that 90% of farmers have low knowledge, 80% of farmers have a negative attitude towards pesticide use, and farmers use incomplete PPE when using pesticides. Agriculture is recommended to increase farmers' knowledge through outreach and education on the safe use of pesticides. The Ranah Bingkuang Farmers Group needs to build communication and provide support to motivate farmers to implement safe and responsible pesticide use. Keywords: Knowledge, Attitudes, and Pesticide Use